Venture capital as a form of international business investment - Pererva, P. G.; Shein, O. S. (Харківський національний університет міського господарства імені О. М. Бекетова, 2025)
The scientific report proves that investing based on venture capital is an important element for stimulating innovative development and supporting entrepreneurship. It helps startups implement their ideas and innovations, which in turn contributes to economic growth and job creation. It is important to remember that successful attraction of international venture capital requires compliance with high standards of governance, transparency and willingness to cooperate with investors.
Венчурний капітал як форма міжнародного інвестування бізнесу
Keywords: investment; venture capital; international activities; business processes; production process; efficiency